Experimental animal infection models for Johne’s disease, an infectious enteropathy caused by Mycobacterium avium subsp. paratuberculosis - Begg, Douglas J.; Whittington, Richard J. (The veterinary journal (1997), 2008)
A critical literature review of experimental infection models for Johne’s disease in farm and laboratory animals was conducted. A total of 73 references were admitted. They were published between 1938 and 2006 and covered species as diverse as cattle, sheep, goats, deer, mice, pigs and others. The factors that appeared to influence the outcome of experimental infections with Mycobacterium avium subsp. paratuberculosis ( Mptb) were the species, breed and age of subject used for the infection, the route of infection, and the strain, dose and number of doses of Mptb used to inoculate the subjects. Natural paratuberculosis infection passes through stages, generally over a period measured in years. However, the endpoints chosen by researchers using experimental infections have been determined by the need for immunological, microbiological, pathological or clinical outcomes, and these were the likely factors determining the duration of the trials. Studies have been lacking in the use of a defined type strain of Mptb in pure culture prepared from an archived seed stock of Mptb that can be used at the same passage level in a later trial. Replication of experimental groups has been very uncommon, temporal replication equally rare, as have sufficiently long time scales so as to be able to observe a full range of immunological and pathological changes at different stages of the disease process. While it may be difficult to develop a satisfactory experimental infection model, there is room for improvement in the way experiments have been designed and carried out to date. Choice of animal species/breed of host and strain of Mptb used in an experimental model should be based on the purpose of the study (for example, vaccine efficacy trial, diagnostic test evaluation, pathogenesis study) and local needs. The strain of Mptb used should be typed using IS900 RFLP analysis, IS1311 sequence analysis and other genotypic methods, and preferably be from an archived low passage pure culture with viable bacteria enumerated using a sensitive method rather than from an uncharacterised and unrepeatable tissue homogenate. It is generally agreed that the faecal-oral route is the most important natural route of exposure and the oral route is therefore the preferred route of experimental inoculation to achieve Johne’s disease that closely resembles natural infection.